The basis of International responsibility and its principles towards illegal actions in International Law - Ali Omar Medon,; Ahmad bin Muhammad Husni, (Institut Kajian Rantau Asia Barat, 2013)
This study discusses international responsibility for illegal actions and its governing principles. It is based on the refusal of governments to accept responsibility of the harm they caused to other countries as a result of their illegal actions. It is also based on the absent of clear guidelines and principles that could be used to determine the nature of responsible for such actions. The objective of this study is to explain the nature of responsibility of the countries that cause harms to other countries. It also aims at explaining the principles governing this responsibility. This study uses analysis approach methodology in order to analyze theories which determine the scope of this international responsibility. This study concludes that countries that violate or refuse to commit themselves to international laws will have to abide to laws accepted by the international communities and the countries being violated will have full right to demand compensation from their aggressors.